Effectiveness of synbiotic red dragon fruit yogurt on glucose and oxidative stress in metabolic syndrome rats - Ninik Rustanti; Nyoman Putri Ari Armelinda; Kharisma Dwi Febriandina; Martha Ardiaria; Ayu Rahadiyanti; Mursid Tri Susilo; Adriyan Pramono (AcTion: Aceh Nutrition Journal, 2025)
Metabolic syndrome is still a global health problem, especially in Indonesia. Oxidative stress is related to metabolic syndrome because it is triggered by hyperglycemia. Synbiotic yogurt containing the whole red dragon fruit has antioxidant and synbiotic potential. This study aimed to determine the effect of synbiotic yogurt with whole red dragon fruit on fasting blood glucose (FBG) and malondialdehyde (MDA) levels in rats with metabolic syndrome. The design of this study was true-experimental, with a pre-post test and randomized control group design. A total of 24 male Sprague Dawley rats were divided into four groups (K-, K+, P1, P2). Groups K+, P1, and P2 were fed a high-fat, high-fructose diet (HFHFD) for 2 weeks. Groups P1 and P2 were administered synbiotic yogurt intervention of 0,009 mL/gBB/day and 0,018 mL/gBB/day, respectively, for 4 weeks. GOD-PAP method for FBG analysis and TBARS method for MDA analysis.  Data were analyzed using the paired t-test and One-Way ANOVA test. The P1 and P2 groups experienced a significant decrease in FBG levels by 63,45% and 76,07%, respectively (p<0,001), and a significant decrease in MDA by 26,1% and 37,2%, respectively (p<0,001). In conclusion, the administration of synbiotic yogurt at 0,018 mL/gBB/day (200 mL/day for humans) for four weeks was effective in reducing FBG and MDA levels.